A Framework for Developing Secondary Markets for Government Securities - Arvai, Zsofia; Heenan, Geoffrey (Washington, D.C. : International Monetary Fund, 2008)
This paper consolidates previous work on the development of secondary markets for government securities, and focuses on the sequencing of measures necessary for their development. Six main lessons are identified: (i) a commitment to achieving and maintaining a stable macroeconomic environment, especially prudent fiscal policy, should underpin market development; (ii) a sound and transparent public debt management strategy supports secondary market activity; (iii) a deep and diverse investor base is required; (iv) poor market infrastructure leads to high transaction costs, slow order execution, and excessive operational risk, which all inhibit trading; (v) secondary market growth is facilitated by effective monetary policy implementation; and (vi) reforms should be sequenced to ensure even development of all the structures supporting the secondary market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet